Diagnostic performance of CT-guided percutaneous transthoracic core needle biopsy using low tube voltage (100 kVp): comparison with conventional tube voltage (120 kVp). (April 2018) - Lee, Han Na; Lee, Sang Min; Choe, Jooae; Lee, Sang Min; Chae, Eun Jin; Do, Kyung-Hyun; Seo, Joon Beom
Background: Computed tomography (CT)-guided percutaneous transthoracic core needle biopsy (PTNB) is typically performed at 120 kVp tube voltage. However, there is no study that has demonstrated diagnostic performance including ground-glass nodules and radiation dose reduction at lower tube voltage in large population. Purpose: To retrospectively compare the diagnostic performance and radiation dose between 100 kVp and 120 kVp during CT-guided PTNB. Material and Methods: This study included 393 PTNBs performed in 385 patients (Group I; 120 kVp) from March 2011 to September 2011 and 1368 PTNBs performed in 1318 patients (Group II; 100 kVp) from October 2011 to December 2013. The patients underwent CT-guided PTNB with the coaxial technique. Diagnostic performance, complication rate, and radiation dose were compared between two groups. Results: Technical success was achieved in 391 of 393 PTNBs (99.5%) in Group I and in 1344 of 1368 PTNBs (98.2%) in Group II ( P  = 0.09). The diagnostic accuracies for pulmonary lesions were not significantly different between two groups (97.1% [362/373] versus 96.2% [1202/1249], P  = 0.458). Complication rate showed no significant differences between two groups in terms of pneumothorax (19.7% [77/391] versus 19.4% [261/1344], P  = 0.904) and hemoptysis (2.3% [9/391] versus 3.2% [43/1344], P  = 0.360). Among patients who developed pneumothorax, three patients (3.9%, 3/77) in Group I and eight patients (3.1%, 8/261) in Group II required treatment with drainage catheter. Nobody needed further treatment for hemoptysis in the two groups. The mean radiation dose was 1.5 ± 1.9 mSv in Group I and 0.7 ± 0.3 mSv in Group II ( P  < 0.001). Conclusion: The 100-kVp protocol for CT-guided PTNB showed significant benefit of radiation dose reduction while maintaining high diagnostic accuracy and safety.